Consumer Animosity and Campaign Intensity as Drivers of Boycott Participation: The Mediating Role of Boycott Intention - Cha Cha Windiati; M. Irfani Hendri; Bintoro Bagus Purmono; Nur Afifah; Juniwati (Journal of Educational Management Research, 2026)
The phenomenon of consumer boycotts against global brands is growing stronger as public attention to corporate ethical and humanitarian issues increases. This study aims to analyze the influence of Consumer Animosity and Boycott Campaign Intensity on Boycott Participation with Boycott Intention as a mediating variable on Unilever Indonesia products. The study used a quantitative approach with a survey method of 332 respondents in Indonesia who had consumed Unilever products and were aware of the boycott campaign. Data were analyzed using covariance-based Structural Equation Modeling (CB-SEM) through AMOS. The results showed that Consumer Animosity and boycott campaign intensity had a positive and significant effect on Boycott Intention. Furthermore, Boycott Intention was proven to be the main determinant that drove Boycott Participation and significantly mediated the influence of both independent variables on boycott participation. These findings conclude that boycott behavior is influenced by emotional factors and social mobilization simultaneously, which strengthen consumer involvement in collective action. This study provides strategic implications for companies in managing their reputation and responding to public ethical issues.